Closely-related Xanthomonas citri subsp. Citri isolates trigger distinct histological and transcriptional responses in Citrus limon - Orce, Ingrid Georgina (2016)
Citrus canker, caused by Xanthomonas citri subsp. citri (Xcc), has an important economic impact on the citrus industry. Extensive information is available about the disease but, nevertheless, the study of plant-pathogen interactions could provide new information in the understanding of citrus canker disease. A new isolate has been identified, Xcc AT, which has a high genetic similarity (> 90 %) to the virulent Xcc T strain based on genetic clustering analyses of the rep-PCR fingerprinting patterns, but it does not produce cankerous lesions in Citrus limon. In this study, we compared C. limon responses to Xcc AT and to the virulent Xcc T strain at both histological and transcriptional levels. Histologically, leaves inoculated with Xcc AT exhibited neither a typical disordering of the spongy mesophyll, nor a swelling of epidermis. A particular content (undetermined) was also found in mesophyll cells near the stomata, together with increased starch accumulation. The transcriptomic profiles were compared by cDNA-AFLP technique. A total of 121 fragments derived from transcript (TDF) were either specifically induced or repressed by the isolates, and 62 were sequenced. Analysis of global expression identified different classes of genes known to be involved in plant-pathogen interactions. This study constitutes the first approach of the specific interaction between the avirulent Xcc AT isolate and C. limon.